Screening extended families for identification of β-thalassemia carriers: an experience from north Maharashtra region - Ismail, Mohammad (International Journal Of Community Medicine And Public Health, 2022)
Background: Beta thalassemias are group of autosomal recessive disorders of hemoglobin synthesis affecting many people worldwide. The study was undertaken to identify carriers of β-thalassemia through extended family screening in communities with high preference of consanguineous marriage. Methods: Ninety families consisting of 130 index cases (β-thalassemia major) with 3466 living family members were approached for testing, of these 1702 were tested. All carriers and couple at risk received counseling and followed for three years. Results: A total of 629 carriers were identified out of 1702 tested members. Of these 310 were married couples and 319 were unmarried. Of the 310 married couples 116 couples were at high risk for producing affected child as both the partners were carriers. There have been four new marriages and seven engagements. Of these no any new married couples were at risk but one engaged couple was at risk as both being a known carrier. Conclusions: Following index cases is reliable and feasible way to study the inherited hemoglobin disorder in high-risk communities and in communities with high preference of consanguineous marriages. High numbers of carriers and couples at risk were identified by screening a very small number of populations.